The influence of mobility strategy on the modern human talus. Issue 3 (11th December 2019) - Sorrentino, Rita; Stephens, Nicholas B.; Carlson, Kristian J.; Figus, Carla; Fiorenza, Luca; Frost, Stephen; Harcourt‐Smith, William; Parr, William; Saers, Jaap; Turley, Kevin; Wroe, Stephen; Belcastro, Maria G.; et al.
Abstract: Objectives: The primate talus is known to have a shape that varies according to differences in locomotion and substrate use. While the modern human talus is morphologically specialized for bipedal walking, relatively little is known on how its morphology varies in relation to cultural and environmental differences across time. Here we compare tali of modern human populations with different subsistence economies and lifestyles to explore how cultural practices and environmental factors influence external talar shape. Materials and Methods: The sample consists of digital models of 142 tali from 11 archaeological and post‐industrial modern human groups. Talar morphology was investigated through 3D (semi)landmark based geometric morphometric methods. Results: Our results show distinct differences between highly mobile hunter‐gatherers and more sedentary groups belonging to a mixed post‐agricultural/industrial background. Hunter‐gatherers exhibit a more "flexible" talar shape, everted posture, and a more robust and medially oriented talar neck/head, which we interpret as reflecting long‐distance walking strictly performed barefoot, or wearing minimalistic footwear, along uneven ground. The talus of the post‐industrial population exhibits a "stable" profile, neutral posture, and a less robust and orthogonally oriented talar neck/head, which we interpret as a consequence of sedentary lifestyle and use of stiff footwear. Discussion: We suggest that talar morphological variation is related to the adoption of constraining footwear in post‐industrial society, which reduces ankle range of motion. This contrasts with hunter‐gatherers, where talar shape shows a more flexible profile, likely resulting from a lack of footwear while traversing uneven terrain. We conclude that modern human tali vary with differences in locomotor and cultural behavior.